Fatores determinantes do Greenwashing em companhias brasileiras - Peixoto, Nathália Oliveira (2024)
Growing concern about social, environmental and governance issues encourages companies to signal good ESG actions to the market and stakeholders. This process can lead to greenwashing, defined as the act of companies disclose more than they actually do in search of reputation and legitimacy. Based on it, the present study aimed to investigate the determining factors for greenwashing in publicly traded Brazilian companies that make them more likely to engage in this practice. The research sample covers 96 publicly held companies from B3, between the period 2013 and 2022. Using the methodology adapted from Yu, Luu and Chen (2020), it was necessary to calculate the greenwashing score based on the ESG disclosure indexes from Bloomberg® and of ESG performance indexes from Refinitiv Thomson Reuters®. To collect data on the other variables, Economatica® and Refinitiv Thomson Reuters® were used. It was applied descriptive statistics, correlation and panel data regression with random effects. As a result, it was found that Brazilian companies have four determining factors for the practice of greenwashing, namely: corporate governance, independence of the audit committee, financial leverage and sector. Specifically, companies that adopt differentiated corporate governance practices, have independent members on the audit committee, are highly leveraged and do not belong to sensitive sectors are less likely to engage in greenwashing and may be more engaged in improving its image and reputation through effective ESG performance and disclosure.